ON THE 10-LEVEL MARK-SYSTEM FOR ESTIMATION OF KNOWLEDGE - Boris G. Lysikav (Высшее образование в России, 2022)
The paper substantiates the necessity for transition from the 50level mark0system forestimation of knowledge of pupils and students to a 100level one in Russia. The techniques for construction the logical, clear, harmonious and common 100level mark0system are developed.